2009
DOI: 10.2215/cjn.06661208
|View full text |Cite
|
Sign up to set email alerts
|

Bone–Vascular Axis in Chronic Kidney Disease

Abstract: C hronic kidney disease (CKD) is characterized by changes in mineral metabolism associated with alterations of its hormonal regulation and various forms of bone disease. In the past, these associations focused attention on the kidney-bone axis. The last decade has seen renewed interest on interactions among mineral metabolism disorders and extraosseous and cardiovascular calcifications observed in CKD or end-stage renal disease (ESRD). Vascular calcification is an active process similar to bone formation that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…Both of these conditions will cause bone loss and increase the possibility of AC (60). The evidence suggests the existence of a bone-vascular axis, and vascular mineralization coexists paradoxically with bone demineralization (21,58). MICS is found to play a key role in activating this axis and inducing AC.…”
Section: The Possible Mechanisms For Mics-induced Ac In Ckdmentioning
confidence: 98%
“…Both of these conditions will cause bone loss and increase the possibility of AC (60). The evidence suggests the existence of a bone-vascular axis, and vascular mineralization coexists paradoxically with bone demineralization (21,58). MICS is found to play a key role in activating this axis and inducing AC.…”
Section: The Possible Mechanisms For Mics-induced Ac In Ckdmentioning
confidence: 98%
“…Thus, the old well known relationship between kidney disease and bone ("renal osteodystrophy") is now extended to a new bone-vascular axis (23,26), and bone has even been recently considered as a new endocrine organ at the heart of CKD-MBD (27).…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…26 It has been long recognized that CKD-MBD (formerly referred to as renal osteodystrophy) has a significant impact on vascular calcification. London et al 27 demonstrated that arterial pulse wave velocity and aortic calcification are increased in CKD patients with decreased bone turnover, namely, in those who do not easily incorporate minerals into the bone, but also do not release them from the skeleton (clinical entity known as adynamic bone disease, usually characterized by low or low-normal PTH levels). 27 The search for correlations between such parameters of mineral metabolism as alkaline phosphatase, bone-specific alkaline phosphatase, PTH, calcium and phosphate, BMD, and vascular calcification in CKD has provided no firm conclusions so far.…”
Section: -6mentioning
confidence: 99%
“…London et al 27 demonstrated that arterial pulse wave velocity and aortic calcification are increased in CKD patients with decreased bone turnover, namely, in those who do not easily incorporate minerals into the bone, but also do not release them from the skeleton (clinical entity known as adynamic bone disease, usually characterized by low or low-normal PTH levels). 27 The search for correlations between such parameters of mineral metabolism as alkaline phosphatase, bone-specific alkaline phosphatase, PTH, calcium and phosphate, BMD, and vascular calcification in CKD has provided no firm conclusions so far. It is generally acknowledged, however, that low PTH levels, low alkaline phosphatase activity, and low BMD (indices of low bone turnover) are associated with more extensive vascular calcification.…”
Section: -6mentioning
confidence: 99%
See 1 more Smart Citation